THE ANALYSIS OF PRICE AND TRADING VOLUME OF STOCKS IN THE INFRASTRUCTURE SECTOR LISTED ON IDX BEFORE AND AFTER THE PRESIDENTIAL ELECTION 2019 - Fahira, Suri Rahma; Islahuddin, Islahuddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The purpose of this research is to analyze the market reaction to the presidential election year 2019 indicated by the average price and trading volume of stocks in the infrastructure sector listed on the Indonesia Stock Exchange before and after the Presidential Election. This research used t-test model. It was found that there was no reaction in stock price, both between sectors and within infrastructure sector. While in the volume of trading, there was reaction between sectors, but there was no reaction within infrastructure sector. So, there is market reaction in Indonesia capital market during the event, but the reaction may not be affected by political event. In other words, Indonesian capital market (in this case IDX) did not react to the presidential election